Who are the contingent workers in federal government? - Mastracci, Sharon H.; Thompson, James R. (2009)
To most federal employment means stable work with good pay, good benefits, long-run job security, and opportunities for promotion from the mail room to upper management. The authors' debunk that notion. The authors' definitively establish the presence of a core/ring structure in federal employment. core occupations are permanent full-time, year-round stable positions, whereas ring jobs are comparatively unstable work situations: temporary, part-time, and/or for a specified period of time. Federal personnel administrators increasingly use temporary, contract, on-call, and part-time positions to control costs. Even when we control for individual characteristics - educational attainment and years of experience - we find group characteristics - particularly gender - reduce the chances of working in a permanent federal job. Is this an indictment against the federal government's reputation as a model employer? Perhaps. At the very least, the potential for gender disparity in employment outcomes deserves further study. Contingent arrangements at the agency level deserve a closer look too. - Reproduced.
Keywords: Human resources development; Civil service